2015
DOI: 10.1088/0004-637x/813/2/115
|View full text |Cite
|
Sign up to set email alerts
|

A Solar Coronal Jet Event Triggers a Coronal Mass Ejection

Abstract: We present the multi-point and multi-wavelength observation and analysis on a solar coronal jet and coronal mass ejection (CME) event in this paper. Employing the GCS model, we obtained the real (three-dimensional) heliocentric distance and direction of the CME and found it propagate in a high speed over 1000 km s −1 . The jet erupted before and shared the same source region with the CME. The temporal and spacial relationship between them guide us the possibility that the jet triggered the CME and became its c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The impulsive and collimated events which originate at the edges of active regions and/or sunspots are known as active region jets (AR jets). Numerous studies have been dedicated to understanding the relationship between AR jets and other phenomena such as micro-flares (Chae et al, 1999;Chifor et al, 2008), flares (Chen, Ip, and Innes, 2013;Krucker et al, 2008), hard X-ray emission (Bain and Fletcher, 2009;Krucker et al, 2011;Glesener, Krucker, and Lin, 2012), Coronal Mass Ejections (CMEs) (Liu et al, 2015;Panesar, Sterling, and Moore, 2016;Miao et al, 2017;Sterling, Moore, and Panesar, 2018), type-III radio bursts (Kundu et al, 1995;Raulin et al, 1996;Klassen, Gómez-Herrero, and Heber, 2011;Innes, Cameron, and Solanki, 2011;Chandra et al, 2015;Mulay et al, 2016) and impulsive solar energetic particle events (Nitta et al, 2006;Pick et al, 2006;Nitta et al, 2008;Wang, Pick, and Mason, 2006;Nitta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The impulsive and collimated events which originate at the edges of active regions and/or sunspots are known as active region jets (AR jets). Numerous studies have been dedicated to understanding the relationship between AR jets and other phenomena such as micro-flares (Chae et al, 1999;Chifor et al, 2008), flares (Chen, Ip, and Innes, 2013;Krucker et al, 2008), hard X-ray emission (Bain and Fletcher, 2009;Krucker et al, 2011;Glesener, Krucker, and Lin, 2012), Coronal Mass Ejections (CMEs) (Liu et al, 2015;Panesar, Sterling, and Moore, 2016;Miao et al, 2017;Sterling, Moore, and Panesar, 2018), type-III radio bursts (Kundu et al, 1995;Raulin et al, 1996;Klassen, Gómez-Herrero, and Heber, 2011;Innes, Cameron, and Solanki, 2011;Chandra et al, 2015;Mulay et al, 2016) and impulsive solar energetic particle events (Nitta et al, 2006;Pick et al, 2006;Nitta et al, 2008;Wang, Pick, and Mason, 2006;Nitta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Jets, standard or blowout, have been observed in Hα or EUV in association with white-light CMEs whose eruption can be traced back to the same location in an AR (Liu et al 2005;Liu 2008;Liu et al 2015;Li et al 2015). In particular, Yan et al (2012) studied two successive flares of X-ray class M that occurred in AR 10484 on 22 October 2003.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the eruption of prominence often leads to a CME [95]. Liu et al [96] observed and analyzed the data obtained from SDO, SOHO and STEREO and suggested that solar jet event can trigger a high -speed CME. Their observation was consistent with the three -dimensional model of solar jets proposed by Pariat et al [71].…”
Section: Solar Dynamical Processes IImentioning
confidence: 99%